The turban for the crown: the Islamic revolution in Iran - Arjomand, Saïd Amir (Studies in Middle Eastern history, 1988)
"The Iranian revolution still baffles most Western observers. Few considered the rise of theocracy in a modernized state possible, and fewer thought it might result from a popular revolution. Said AmirArjomand's "The Turban for the Crown" provides a thoughtful, painstakingly researched, and intelligible account of the turmoil in Iran which reveals the importance of this singular event for our understanding of revolutions." --